Human casualties in earthquakes progress in modelling and mitigation - Spence, R. J. S. (Robin J. S.); So, Emily; Scawthorn, Charles (Advances in Natural and Technological Hazards Research, 2011)
Assessment of human casualties in earthquakes has become a topic of vital importance for national and urban authorities responsible for emergency provision, for the development of mitigation strategies and for the development of adequate insurance schemes. In the last few years important work has been carried out on a number of recent events (including earthquakes in Kocaeli, Turkey 1999, Niigata Japan, 2004, Sichuan, China 2008 and L'Aquila,Italy 2009). These events have created new and detailed casualty data, which has not until now been properly assembled and evaluated. This book draws the new evidence from recent events together with existing knowledge. It summarises current trends in the understanding of the factors influencing the numbers and types of casualties in earthquakes; it offers methods to incorporate this understanding into the estimation of losses in future events in different parts of the world; it discusses ways in which pre-event mitigation activity and post-event emergency management can reduce the toll of casualties in future events; and it identifies future research needs. Audience: This book will be of interest to scientists and professionals in engineering, geography, emergency management, epidemiology and the insurance industry.